Pengembangan Aplikasi Pengendalian ATK Dan Mobil Operasional Pada Departemen Umum Pelindo Regional 1 Menggunakan Metode Waterfall - Ganda, Ricky; Hariyanto, Eko; Kurniawan, Fahmi (Fakultas Teknologi dan Ilmu Komputer Universitas Prima Indonesia, 2024)
PT Pelabuhan Indonesia (Pelindo) is an integrated company based on government strategic initiatives. PT Pelindo Regional 1, which is headquartered at Belawan Port-Medan, has a vast working area covering four provinces, causing the need to support Pelindo Regional 1's operational activities to also be significant, such as office stationery (ATK) and operational cars. The use of ATK or operational cars greatly influences the company's operational costs, which can also affect the company's profits. This research aims to design and implement an application for controlling stationery demand and operational car usage so that it can be monitored effectively and efficiently. The methods used are Waterfall and Unified Modeling Language. The results of implementing this application can make it easier for each work division (user) to submit requests for ATK and use of operational cars and obtain application status information. This application makes it easy for the general department (admin) to control requests for stationery and operational cars and obtain information on the total costs used by each work division from requests for stationery and operational cars approved.